Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

Elucidation of the role of hexamine and other precursors in the formation of magnetite nanorods and their stoichiometry - Singh, Hema; Bhagwat, Shrikant; Jouen, Samuel; Lefez, Benoit; Athawale, Anjali A.; Hannoyer, Beatrice; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2010)
Hexamine is known to assist anisotropic growth of metal oxides and the same is also found to be true for magnetite nanosynthesis. In this work we elucidate the role of hexamine and other precursors in the formation of magnetite nanorods by the hydrothermal route and their stoichiometry. Various others hydrolyzing agents such as sodium hydroxide (NaOH), sodium hydroxide + hexamine, ammonia (NH(3)), ammonia + formaldehyde are also studied. The synthesized nanoparticles are characterized with the help of various techniques such as X-ray diffraction (XRD), FT-IR spectroscopy, UV-VIS-NIR spectroscopy, transmission electron microscopy (TEM), Mossbauer spectroscopy and SQUID magnetization measurements. It is found that only when ferric chloride, ferrous ammonium sulfate (FAS) and hexamine are used, well defined nanorods are formed. When sodium hydroxide and hexamine are used as a hydrolyzing system nearly spherical nanoparticles with small size (similar to 13 nm) are formed, as compared to the case of sodium hydroxide alone which leads to bigger cube like nanoparticles. Interestingly the decomposition products of hexamine do not lead to nanorod formation. Thus, slow decomposition of hexamine at elevated temperature and the consequent slow rise in pH is the key to the anisotropic growth of the iron oxide system.